2002
DOI: 10.1074/jbc.m207413200
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction between Myeloid Cell Leukemia 1 Protein (MCL1) and Fortilin

Abstract: Myeloid cell leukemia 1 protein (MCL1) is an antiapoptotic protein that is structurally related to Bcl-2. Unlike other Bcl-2 family proteins that are constitutively expressed, MCL1 is inducibly expressed in cells that are recently exposed to growth and differentiation stimuli. Here, we report the identification of fortilin as a novel MCL1-interacting protein by screening of a yeast two-hybrid library with MCL1 as bait. Fortilin specifically interacted with MCL1 both in vitro and in vivo. The intracellular loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 30 publications
6
131
3
Order By: Relevance
“…This situation is strikingly similar to the one described here for TCTP. Interestingly, Mcl-1 has been described as a protein stabilizing TCTP (Zhang et al, 2002) and vice versa (Liu et al, 2005). These results are compatible with a model according to which activation of PKR by proapoptotic stimuli results in an increase in eIF2a phosphorylation and downregulation of antiapoptotic proteins (Scheuner et al, 2006), such as TCTP (Figure 7) or Mcl-1 (Fritsch et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This situation is strikingly similar to the one described here for TCTP. Interestingly, Mcl-1 has been described as a protein stabilizing TCTP (Zhang et al, 2002) and vice versa (Liu et al, 2005). These results are compatible with a model according to which activation of PKR by proapoptotic stimuli results in an increase in eIF2a phosphorylation and downregulation of antiapoptotic proteins (Scheuner et al, 2006), such as TCTP (Figure 7) or Mcl-1 (Fritsch et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Our observations on both the pattern of PKR-dependent downregulation of TCTP under Ca þ þ -stress conditions and on the cytoprotective function of TCTP 6) also suggest that the protein has broader antiapoptotic effects. Several reports support the view that TCTP undergoes direct interactions with the apoptotic machinery (Zhang et al, 2002;Liu et al, 2005;Yang et al, 2005;Susini et al, 2008) The antiapoptotic protein Bcl-xL, with which TCTP interacts, is involved in maintaining Ca þ þ homeostasis in the ER (Xu et al, 2005) and it is, therefore, possible that involvement of TCTP in the cell's response to Ca þ þ stress is based on this interaction. It was recently reported that translational downregulation of another antiapoptotic protein, Mcl-1, is an important permissive step in the apoptotic events induced by cell-stress reagents such as tunicamycin, thapsigargin and arsenite (Fritsch et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mcl-1 (Liu et al 2005;Zhang et al 2002) and Bcl-XL ). In the case of Mcl-1, it was reported that TCTP stabilises Mcl-1 (Liu et al 2005) and vice versa (Zhang et al 2002), but another study also showed that both proteins are able to exert their anti-apoptotic activity independently of each other . Recently, the interaction of TCTP with Bcl-XL was investigated in more detail (Thebault et al 2016).…”
Section: Stress Responsementioning
confidence: 99%
“…There are a few reports, which indicate that in specific instances TCTP protein may be subject to regulated degradation. Two studies described the ability of another anti-apoptotic protein, Mcl-1 (Zhang et al 2002), and heat-shock protein Hsp27 (Baylot et al 2012) to stabilise the TCTP protein, which implies that it may be destabilised if those proteins are absent. Kubiak et al reported that TCTP, a protein involved in maintaining the integrity of the mitotic spindle, is partially degraded during mitotic exit (Kubiak et al 2008).…”
Section: Other Post-transcriptional Regulationmentioning
confidence: 99%